Climate Change Adaptation in Regional Planning—A Germany-Wide Analysis on the State of Implementation of Adaptation-Relevant Regional Plan Contents - Schmitt, Hanna Christine (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Since the publication of the German Strategy for Adaptation to Climate Change there has been scientific and planning political consensus on the ability of regional planning to implement climate change adaptation contents. To which extent the formal regional spatial planning meets this ability, is the key issue of this article. The analysis is a census for the regional planning territories of Germany. Their regional plans are examined regarding the presence and bindingness of adaptation-relevant designations. The action plan of spatial planning on prevention, mitigation and adaptation strategies with regard to the spatial consequences of climate change of the Conference of Ministers on Spatial Planning and its seven adaptation-related fields of action serve as a basis for the analysis. As a result, the state of implementation of adaptation-relevant regional plan contents is presented—both for each field of action as well as comprehensively. Furthermore, the results are reflected and further adaptation potentials are presented.
Keywords: Regional planning; Climate change; Climate change adaptation; Adaptation; Adaptive capacity; Germany